Solving the Labour Problem at Imperial Oil: Welfare Capitalism in the Canadian Petroleum Industry, 1919-1929 - Grant, Hugh (Labour/Le Travailleur, 1998)
Abstract Facing industrial unrest in each of its Canadian petroleum refineries, the Imperial Oil Company embarked on a wide-ranging industrial-relations initiative in 1919. Patterned after Mackenzie King's "Rockefeller Plan," the logic was clear: joint worker-management councils would alleviate shop-floor discontent; a package of welfare benefits would reduce absenteeism and turnover; and a share-purchase plan would enhance worker loyalty to the Company. Where similar attempts at corporate welfarism in Canada generally failed, Imperial Oil enjoyed a union free status until 1946, and freedom from work stoppages until the early 1950s. What made it unique in this regard was its willingness and capacity to buy labour harmony; and in an era hostile to organized labour, its workers succeeded in extracting important monetary concessions as the price of their loyalty. Imperial Oil thus offers a cogent example of the conditions necessary for King's variant of welfare capitalism to flourish.